Developing Personal Care Programs: National Trends and Interstate Variation, 1992-2002 - Martin Kitchener; Terence Ng; Helen Carrillo; Nancy Miller; Charlene Harrington (SAGE Publishing, 2007)
This paper examines the development of programs delivering personal care to the elderly and disabled. First, we report the latest national participant and expenditure trend data for the three main personal care programs: the Medicaid Personal Care Services (PCS) benefit, Medicaid 1915(c) waivers, and the Older Americans Act Title III. Second, to examine interstate variation revealed in the trend analysis, we present three time-series regression models of personal care development (expenditures, participants, and existence of PCS benefit) that control for state socioeconomic, political, policy, and provider characteristics. Positive predictors of personal care development include: percentages of population aged 85 and older, and nonwhite; per capita income; and liberal state politics. Negative predictors of personal care development include rates of Medicare home health users and hospital beds.